2015
DOI: 10.1016/j.crvasa.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Early discharge (within 72 h) in low risk patients after acute ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention. Single centre experience

Abstract: V uplynulých dekádách bylo možné sledovat jasný trend ke zkracování pobytu v nemocnici u pacientů s infarktem myokardu s elevacemi úseku ST (STEMI). Aktuální doporučení Evropské kardiologické společnosti pro léčbu STEMI uvádějí, že u vybraných pacientů může být zvážena časná dimise (po přibližně 72 hodinách), pokud je zajištěno adekvátní navazující sledování. Autoři prezentují prospektivní analýz u 25 nízce rizikových pacientů se STEMI, léčených úspěšnou primární perkutánní koronární intervencí (PCI) a propušt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…tested safety hypothesis of discharge within 48 to 56 hours as opposed to usual discharge, and reported no difference in all-cause mortality (0.6% vs. 0.8%; p = 0.369) and readmission (3.8% vs. 6.9%; p = 0.061) rate after 30-days of discharge respectively. Similarly, many other studies conducted in various parts of the world showed evidence in favor of the early discharge (≤ 72 hours) strategy [11][12][13][14]23]. However, evidence regarding safety of same day (≤ 24 hours) discharge strategy in setting of primary PCI is very limited as safety of this strategy after successful ad hoc or elective PCI has been reported by only a few studies [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…tested safety hypothesis of discharge within 48 to 56 hours as opposed to usual discharge, and reported no difference in all-cause mortality (0.6% vs. 0.8%; p = 0.369) and readmission (3.8% vs. 6.9%; p = 0.061) rate after 30-days of discharge respectively. Similarly, many other studies conducted in various parts of the world showed evidence in favor of the early discharge (≤ 72 hours) strategy [11][12][13][14]23]. However, evidence regarding safety of same day (≤ 24 hours) discharge strategy in setting of primary PCI is very limited as safety of this strategy after successful ad hoc or elective PCI has been reported by only a few studies [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the advancements in the management strategies and use of evidence based pharmacological therapies, there is a growing trend of reduced hospital stay for STEMI patients [ 9 10 ]. Feasibility, safety, and cost-effectiveness of the reduction of post-procedure hospital stay in selected low-risk STEMI patients has been demonstrated by some of the recent studies [ 11 12 13 14 ]. Randomized studies conducted thus far have established safety and feasibility of ≤ 72 hours post-procedure discharge strategy [ 11 14 15 16 17 ] and 48 to 56 hours post-procedure discharge strategy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benha University, Benha, Egypt. 2 King Abdullah Medical City, Muzdallfa Road, Makkah, Saudi Arabia. 3 Zagazig University, Zagazig, Egypt.…”
Section: Fundingmentioning
confidence: 99%
“…Shortening of the hospital stay in patients admitted with the diagnosis of acute myocardial infarction (AMI) has been observed within the last decades [1][2][3].…”
Section: Introductionmentioning
confidence: 99%